Development of Web-Based Sepak Takraw Learning Media - Lisa Anggraeni; Iyakrus Iyakrus; Herri Yusfi; Wahyu Indra Bayu; Meirizal Usra; Syafaruddin Syafaruddin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This research aims to produce web-based sepak takraw learning media as a learning resource for Physical Education and Physical Education students at FKIP Sriwijaya University. The type of research used is research and development (R&D). The population in this research were all students in the third semester of Physical Education, FKIP, Sriwijaya University. The sample for the small-scale test in this study was twenty-three third semester physical education students. The large-scale trial consisted of sixty-five third semester Physical Education students. The instruments in this research are data collection using validation sheets, questionnaires, and student learning outcomes tests. Data analysis techniques include validity, practicality analysis and effectiveness analysis. Based on the research results obtained from this research, the sepak takraw learning media is said to be very valid, seen from the validation results for the average score for all aspects of the assessment of 4.45 in the very valid category. From the student response questionnaire, this learning media was said to be practical to use by getting a practicality score of 3.81 in the very positive category. Based on the results of student learning tests, the web-based sepak takraw learning media, namely as a learning resource for Physical Education and Physical Education students, FKIP, Sriwijaya University, is said to be effective to use. The test results from the learning outcomes obtained 90.9% completeness which is included in the high category. The conclusion of the research is that the web-based sepak takraw learning media for Physical Education and Physical Education students at FKIP Sriwijaya University is stated to be very valid, in its use this media is also said to be practical in the positive category and this media is also effective for use as a support for learning process activities because it is in the high category.